The EORTC QLU-C10D: The Canadian Valuation Study and Algorithm to Derive Cancer-Specific Utilities From the EORTC QLQ-C30. Issue 1 (April 2019) - McTaggart-Cowan, Helen; King, Madeleine T.; Norman, Richard; Costa, Daniel S. J.; Pickard, A. Simon; Regier, Dean A.; Viney, Rosalie; Peacock, Stuart J.
Objective. The EORTC QLQ-C30 is widely used for assessing quality of life in cancer. However, QLQ-C30 responses cannot be incorporated in cost-utility analysis because they are not based on general population's preferences, or utilities. To overcome this limitation, the QLU-C10D, a cancer-specific utility algorithm, was derived from the QLQ-C30. The aim of this study was to obtain Canadian population utility weights for the QLU-C10D.Methods. Respondents from a Canadian research panel expressed their preferences for 16 choice sets in an online discrete choice experiment. Each choice set consisted of two health states described by the 10 QLU-C10D domains plus an attribute representing duration of survival. Using a conditional logit model, responses were converted into utility decrements by evaluating the marginal rate of substitution between each QLU-C10D domain level with respect to duration.Results. A total of 3, 363 individuals were recruited. A total of 2, 345 completed at least one choice set and 2, 271 completed all choice sets. The largest utility decrements were associated with the worse levels of Physical Functioning (−0.24), Pain (−0.18), Role Functioning (−0.15), Emotional Functioning (−0.12), and Nausea (−0.12). The remaining domains and levels had decrements of −0.05 to −0.09. The utility of the worst possible health state was −0.15.Conclusion. Respondents from the general population were most concerned with generic health domains, but Nausea and Bowel Problems also had an impact on the individual's utility. It is unclear as to whether cancer-specific domains will affect cost-utility analysis when evaluating cancer treatments; this will be tested in the next phase of the study.